Determinants of Farmers’ Engagement in Off-Farm (Non-Farm Activities) as Copping Strategies to Climate Change: The Case of Merti, Arsi Zone, Oromiya Regional State, Ethiopia - Eshete, Mulugeta (International Journal of Climate Research, 2017)
Climate change is happening at a great speed becoming gradually perceived as most challenging impact of the world that life bearing organisms on earth ever sense. The study identified determinants of farmers’ engagement in non-farm activities as copping strategies to climate change in Merti, Arsi zone, Oromiya Regional state, Ethiopia. The studies also carried out to investigated gender differences in perceiving climate change, assess non-farm activities practiced by farmers in response to climate change and describe the determinant factors that influence farmers’ engagement in off-farm income source in the study area. The study followed a multi-stage sampling procedure. Both purposive and random sampling procedures were used to select sample Kebeles and households, respectively. Data collected from 191 sample households was used in this study. Descriptive statistics were performed to assess farmers perceptions and the types of coping strategies used were small-scale trade activities, handicrafts/craftsmanship and engagement in labor intensive salaried work, while the multinomial logit model (MNL) was used to identify factors influencing farmers coping strategies to climate change whereas age, sex, family size, agro-ecological locations (highland and midland), perception of climate change were the determinant factors favoring or inhibiting the decisions of farming households engagement in non-farm activities as climate change coping strategies.